Re: Tool-Kit for Detroit - Beebe, Heidi (ARCC Conference Repository, 2014)
Detroit is a city defined by making. The refrain "You can get anything made in Detroit” is often quoted today even after the decline and relocation of the automotive industry. Given the condition of Detroit, the state of American manufacturing, and the fact that the city and its fabrication networks are illegible to newcomers and industry outsiders, the Re:Tool-Kit for Detroit research project questions the veracity of this claim. The project asks what can you really get made in Detroit today. Who are the makers operating in the city today? Where are the fabrication shops? How does fabrication shape the city today? And how is theculture of making in Detroit evolving in response to the changes in manufacturing, the rise of digital fabrication, and an influx of artist and craft based making? By mapping the fabrication landscape of the city, and packaging the research in a way that is accessible to designers, and students of art, architecture and design who may not be fabricators, the research seeks to create new opportunities for the under utilized fabrication capacity that already exists in Detroit and to encourage new collaborations between university and city, design and fabrication. Research for this study was gathered through 47 interviews conducted with a range of fabricators. Interviews were recorded and analyzed. Fabrication shops and fabricators were documented photographically and mapped. The research findings have been exhibited at the University of Michigan and will be available in the form of awebsite and a printed (and printable) "toolkit” both of which contains a map, directory, journalistic case studies, and a series of historical vignettes documenting previous examples of industrial production collaborating with art and design in the city of Detroit. The research project has also entered into a partnership with a non-profit "designed to support Detroit’s growing creative economy” called the Detroit Ceative Corridor Center.